KOMPOSISI DAN STRUKTUR RERUMPUTAN DI KAWASAN DANAU TOBA DESA TOGU DOMU NAULI KECAMATAN DOLOK PARDAMEAN KABUPATEN SIMALUNGUN SUMATERA UTARA - Pinta Omas Pasaribu; M Zaidun Sofyan; Nursahara Pasaribu (Saintia Biologi, 2013)
The composition and structure of grasses in Toba Lake Area Togu Domu Nauli Village, Dolok Pardamean Subdistrict, Simalungun Regency, North Sumatra has been studied from March to June 2012. The study site is determined by purposive sampling method and it is divided three locations based on altitude with 20 plots of  1 x 1 m size for each area. There are 21 species of grasses that belong to two families found at three study sites. The first area was dominated by Imperata cylindrica, the second was dominated by Leersia hexandra, and the third was dominated by Imperata cylindrica with importance values are 58.408 %, 72.202 %, and 81.316 %, respectively. The diversity index (H’) of grasses are 1.826, 1.432, 1.010 at area I, II, and III, respectively and equitability index (E) of grasses are 0.658, 0.597, 0.519 at area I, II, and III, respectively. The Similarity index of grasses ranges from 46.91% to 62.56%, with the highest similarity index is 62.56%  that is found between area II and III.   Keyword : Composition, grasses, Simalungun, structure.